The addition of CD38 monoclonal antibody to triplet regimens improves survival in newly diagnosed multiple myeloma with high-risk cytogenetics: a systematic review and meta-analysis of randomized controlled trials - Hu, Bin; Fang, Dan; Jiang, Ling; Li, Tianqi; Chen, Kexia; Cao, Jinxia; Wang, Jun (Frontiers in Immunology, 2026)
BackgroundThe efficacy of CD38 monoclonal antibody (mAb)-based quadruplet regimens versus triplet regimens in newly diagnosed multiple myeloma (NDMM) patients with high-risk cytogenetics remains controversial. This meta-analysis aims to consolidate evidence from randomized controlled trials (RCTs) to resolve this clinical uncertainty.MethodsWe systematically searched PubMed, EMBASE, and the Cochrane Library for RCTs comparing CD38 mAb-based quadruplet regimens with triplet regimens in NDMM patients with high-risk cytogenetics. The primary outcomes were the rate of minimal residual disease (MRD) negativity at a sensitivity of 10-5 and progression-free survival (PFS).ResultsNine RCTs comprising 4557 patients were included. Compared to triplet regimens, CD38 mAb-based quadruplet regimens were associated with a significantly higher rate of MRD negativity (pooled OR = 2.02, 95% CI: 1.41-2.88, P = 0.0001) and a significantly improved PFS (pooled HR = 0.74, 95% CI: 0.59-0.94, P = 0.01). However, subgroup analyses revealed that the PFS benefit was not significant for isatuximab-based quadruplet regimens (pooled HR = 1.04, 95% CI: 0.67-1.62, P = 0.84) or in transplant-ineligible patients (pooled HR = 0.79, 95% CI: 0.56-1.13, P = 0.19).ConclusionThe incorporation of CD38 mAbs, particularly daratumumab, into triplet regimens improves depth of response and PFS in NDMM patients with high-risk cytogenetics.Systematic review registrationhttps://inplasy.com/inplasy-2025-10-0103/, identifier INPLASY2025100103.